Spatial gradients in ratios of atmospheric trace gases: a study stimulated by experiments on bird navigation - WALLRAFF, HANS G.; ANDREAE, MEINRAT O. (Tellus. Series B, Chemical and physical meteorology, 2000)
Numerous experiments with homing pigeons and other birds strongly suggest that birds displaced to unfamiliar remote areas are able to determine their position relative to home by deducing relevant information from atmospheric trace gases perceived by olfaction. These findings induced the hypothesis that ratios between several airborne compounds show roughly monotonic spatial gradients, differently in different directions, over distances of some hundreds of kilometres. To test this hypothesis, 192 air samples were collected, successively in 3 summers, at 96 sites regularly distributed over an area covering a radius of 200 km around Würzburg, Germany. Statistical analysis of the gas chromatographic measurements on these samples revealed that such gradients in the ratios between a number of omnipresent hydrocarbons do in fact exist. The gradients are noisy, but not beyond the range that is compatible with the homing behaviour of pigeons which is noisy as well. The directions of the gradients are remarkably robust against changes of weather, especially of winds. Winds, however, shift the levels of ratios in the whole area without dramatically changing the directional relationships. A systematic angular correlation between variations in space and variations caused by winds could theoretically be utilized by birds for navigational purposes. Our analysis dealt mainly with the most abundant anthropogenic hydrocarbons, which are the best‐suited tracers to detect spatio‐temporal distribution patterns. It is very likely that equivalent patterns exist in naturally emitted volatile compounds as well, given that they are subject to similar variability in the distribution of sources and sinks and similar transport patterns.